Concentration effect of prostaglandin E2 on the growth factor expression and cell proliferation in bovine endometrial explants and their kinetic characteristics. (28th October 2017) - Zhang, S; Mao, W; Li, Q; Gao, R; Zhang, Y; Gao, L; Fu, C; Wu, J; Deng, Y; Shen, Y; Li, T; Liu, B; et al.
Contents: Bovine endometrium undergoes various physiological and histological changes that are necessary for blastocyst implantation during oestrous cycle. From pro‐oestrus to late‐oestrus, endometrium thickens gradually for implantation preparation and exhibits remarkable capacity for self‐repair after uterine lining shedding while implantation does not occur. The prostaglandin E2 (PGE2 ) secretion pattern is synchronized with endometrial growth during oestrous cycles in bovine endometrium; however, limited information is available regarding the association between PGE2 secretion and endometrial growth. In this study, the concentration (10 −9 to 10 −5  M) and time effect (2–36 hr) of PGE2 treatment on a series of growth factors are essential for endometrial growth including connective tissue growth factor (CTGF), fibroblast growth factor‐2 (FGF‐2), interleukin‐8 (IL‐8), transforming growth factor‐β1 (TGF‐β1), matrix metalloproteinase‐2 (MMP‐2), and vascular endothelial growth factor A (VEGFA) mRNA and protein expression, and proliferation of epithelial and fibroblast cells was investigated in bovine endometrial explants in vitro. The results indicated that PGE2 at concentration about 10 −7 to 10 −5  M could up‐regulate CTGF, FGF‐2, IL‐8, MMP‐2, TGF‐β1, VEGFA mRNA and protein expression, and could induce the proliferation of epithelial and fibroblast cells and reduce the proapoptotic factor (caspase‐3) expression in bovine endometrial explants in vitro. These results collectively improved the possibility of PGE2 functions in endometrial growth during oestrous cycles.